Treatment of Furfural Wastewater by (AOPs) Photo-Fenton Method (Journal of Engineering, 2015)
The objective of this study is to investigate the application of advanced oxidation processes (AOPs) in the treatment of wastewater contaminated with furfural. The AOPs investigated is the homogeneous photo-Fenton (UV/H2O2/Fe+2) process. The experiments were conducted by using cylindrical stainless steel batch photo-reactor. The influence of different variables: initial concentration of H2O2 (300-1300mg/L), Fe+2(20-70mg/L), pH(2-7) and initial concentration of furfural (50-300 mg/L) and their relationship with the mineralization efficiency were studied. Complete mineralization for the system UV/H2O2/Fe+2 was achieved at: initial H2O2 = 1300mg/L, Fe+2 = 30mg/L, pH=3, temperature =30oC and irradiation time of 60 min, for 300mg/L furfural concentration. The results have shown that the oxidation reagent H2O2 plays a very important role in the furfural mineralization.